The restaurant : from concept to operation - Walker, John R., 1944-. (Hoboken, NJ : Wiley, 2011)
"Restaurant owners will continue to turn to The Restaurant because it helps them gain the skills needed to master every challenge and succeed in this highly competitive and rewarding industry. Each chapter has been revised, updated, and enhanced with numerous industry examples, sidebars, charts, tables, photographs, and menus. Greater emphasis is placed on restaurant business plans, restaurant management, and restaurant operations. The themes of sustainability and sustainable restaurant management have been added throughout. New sections have also been included on purchasing meat, cocktails, and the early history of eating out. All of this information will help restaurant owners make the decisions necessary to build a thriving business."--
Machine generated contents note: Chapter 1: Introduction -- Chapter 2: Kinds and Characteristics of Restaurants and Their Owners -- Chapter 3: Concept, Location, and Design -- Chapter 4: The Menu -- Chapter 5: Planning and Equipping the Kitchen -- Chapter 6: Food Purchasing -- Chapter 7: Bar and Beverages -- Chapter 8: Operations, Budgeting, and Control -- Chapter 9: Food Production and Sanitation -- Chapter 10: Restaurant Leadership and Management -- Chapter 11: Organization, Recruiting, and Staffing -- Chapter 12: Employee Training and Development -- Chapter 13: Service and Guest Relations -- Chapter 14: Technology in the Restaurant Industry -- Chapter 15: Restaurant Business and Marketing Plans -- Chapter 16: Financing and Leasing -- Chapter 17: Legal and Tax Matters.
Keywords: Restaurant management